THE IMPLEMENTATION OF PRECEPTORSHIP MODEL IMPROVE COMPETENCY ACHIEVEMENT OF NURSING CLINICAL STUDENTS - Siska Mayang Sari; Ennimay Ennimay; Erna Marni; Yeccy Anggreny (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2017)
Nursing clinical study as purpose to create a nurse graduate which have competency include cognitive, skills and good manner, be able to give nursing  and health services with apply the nursing principles and rules in the  health system services. The achievement of student’s competency is obtain by selection of appropriate of learning models. Preceptor ship is one of the learning model in clinical study. The research aims to analyze the implementation of preceptor ship model toward competency achievement of nursing clinical students. This first years is a observational quantitative study. Samples was taken by consecutive sampling to 38 preceptees and 38 preceptors. The data was taken by checklist instrument. The data processing used univariate and bivariate within chi-square. The results showed that 20 (52.6%) preceptors were good in preceptor ship implementations and 18 (47.6%) preceptors were less good. While that the competency of student’s achievement results showed that amount 21 (53.3%) were achieved and amount 17 (44.7%) were half achieved. Chi-square result showed that p-value 0.010 (<0.05) which means there were correlation between implementation of preceptorship model toward competency achievement of nursing clinical students. This research recommended preceptor ship model into clinical learning towards enhance the competency achievement of students.